PENGARUH KESULITAN KEUANGAN, MOTIVASI PAJAK, DAN KARAKTERISTIK PERUSAHAAN TERHADAP MANAJEMEN LABA - Sugito, Jesica; Wijoyo, Dewi Sari (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to determine whether financial distress, tax motivation, return on asset, financial leverage, sales growth, company size, and free cash flow have an influence on earnings management. The sample used in this study consists of consumer cyclicals and consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during 2019 - 2022, totalling 62 selected companies as the research sample. The sample selection is conducted by using purposive sampling method, resulting in 62 companies for this research. The analysis utilized a multiple linear regression model. The findings indicate that financial distress, financial leverage, and sales growth have a positive impact on earnings management. This implies that higher levels of financial distress, financial leverage, and sales growth increase the likelihood of earnings management within a company. On the other hand, asset returns and free cash flow show a negative influence on earnings management. This implies that higher levels of, asset returns and free cash flow reduce the likelihood of earnings management practices within a company. Furthermore, variables such as tax motivation and company size do not affect earnings management, indicating that regardless of the figures related to tax motivation and company size, they do not influence the likelihood of earnings management within a company.